2013
DOI: 10.7895/ijadr.v2i3.116
|View full text |Cite
|
Sign up to set email alerts
|

Screening in treatment programs for Fetal Alcohol Spectrum Disorders that could affect therapeutic progress

Abstract: Grant, T., Novick Brown, N., Graham, J., Whitney, N., Dubovsky, D. , & Nelson, L. (2013). Screening in treatment programs for Fetal Alcohol Spectrum Disorders that could affect therapeutic progress. The International Journal Of Alcohol And Drug Research, 2(3), 37-49. doi:10.7895/ijadr.v2i3.116 (http://dx.doi.org/10.7895/ijadr.v2i3.116)Aims: While structured intake interviews are the standard of care in substance abuse treatment programs, these interviews often do not screen for cognitive impairments, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
1
15
1
Order By: Relevance
“…These factors can lead to the development of secondary disabilities in adolescence and adulthood, including educational disruption, legal trouble, difficulty securing or keeping a job, confinement in psychiatric institutions or jail, inappropriate sexual behavior, and substance use disorders (Blaschke et al, 2009). Another troubling finding is that affected females have a higher risk of having an alcohol-or substance-exposed pregnancy themselves (Grant et al, 2013). Most individuals with FASDs need ongoing social support and mental health services.…”
Section: Secondary Disabilitiesmentioning
confidence: 99%
“…These factors can lead to the development of secondary disabilities in adolescence and adulthood, including educational disruption, legal trouble, difficulty securing or keeping a job, confinement in psychiatric institutions or jail, inappropriate sexual behavior, and substance use disorders (Blaschke et al, 2009). Another troubling finding is that affected females have a higher risk of having an alcohol-or substance-exposed pregnancy themselves (Grant et al, 2013). Most individuals with FASDs need ongoing social support and mental health services.…”
Section: Secondary Disabilitiesmentioning
confidence: 99%
“…Given the high comorbidity of Post-Traumatic Stress Disorder in adults with AUDs, we will assess for the presence of this condition using the MINI [40]. We will also assess for potential Fetal Alcohol Spectrum Disorder using the Life History Screen [54], a brief measure that unobtrusively screens participants for adverse life-course outcomes typically found in FASD. Medical comorbidity will be measured using a modified version of the Charleson Deyo Scale [55], a simple self-report questionnaire assessing the presence of chronic medical conditions.…”
Section: Methodsmentioning
confidence: 99%
“…If the subjects did not understand a question, we used the "B-note" (a predetermined paraphrase) for each question. Overall, previous studies reported that the interview is an easy and quick diagnostic tool 17,24 . The interviews were conducted by well-trained physicians and doctoral students.…”
Section: Study Design and Recruitment Settingmentioning
confidence: 99%
“…The BSI-FASD. The German BSI-FASD version was initially developed by Schwerg and colleagues on the basis of the English LHS 17 . The development of the BSI-FASD was a five step process.…”
Section: Study Design and Recruitment Settingmentioning
confidence: 99%
See 1 more Smart Citation